Surface morphology studies of single and double layer In0.5Ga0.5As/GaAs quantum dots grown by stranski-krastanow growth modes - Aryanto, Didik (Faculty of Science, Universiti Teknologi Malaysia, 2009)
Single and double layer In0.5Ga0.5As/GaAs QDs with various buffer layer thickness were grown by metal-organic chemical vapor deposition (MOCVD) using Stranski-Krastanow growth mode. The effect of buffer layer thickness on a high density QDs has been investigated using atomic force microscopy (AFM). Surface morphology which includes variation in the size and density of the dots on the surface has been studied. A single layer In0.5Ga0.5As QDs with 100 nm and 300 nm GaAs buffer layer shows higher density of QDs with apparently smaller dots size. However, a double layer In0.5Ga0.5As QDs with 25 nm GaAs spacer layer shows different size, uniformity and density compared to a single layer In0.5Ga0.5As QDs. Variation in the surface morphology of the double layer QDs is attributed to the structure of the first QDs and the structure of barrier layer between QDs. Double layer QDs grown using 200 nm GaAs buffer layer and 25 nm spacer layer shows higher dots density and smaller dots in the top most compared to other samples prepared with double layer QDs. This indicates that, the spacer layer structures and dot formation in the under-layer also have important effect on the surface morphology of the double layer (stacked) QDs. However, in the Stranski-Krastanow growth mode, surface morphology and structures of QDs depend strongly on growth parameters.